Cardiac Regeneration by Statin‐Polymer Nanoparticle‐Loaded Adipose‐Derived Stem Cell Therapy in Myocardial Infarction. (3rd June 2019) - Yokoyama, Ryo; Ii, Masaaki; Tabata, Yasuhiko; Hoshiga, Masaaki; Ishizaka, Nobukazu; Asahi, Michio
Abstract: Clinical trials with autologous adipose‐derived stem cell (AdSC) therapy for ischemic heart diseases (IHDs) are ongoing. However, little is known about combinational therapeutic effect of AdSCs and statin poly(lactic‐co‐glycolic) acid (PLGA) nanoparticles on the ischemic myocardium. We investigated the hypothesis that statins, which have pleiotropic effects, augment the therapeutic potential of AdSCs and that AdSCs also act as drug delivery tools. Simvastatin‐conjugated nanoparticles (SimNPs) significantly promoted migration activity without changing proliferation activity and upregulated growth factor gene expression in vitro. A small number of intravenously administered SimNP‐loaded AdSCs (10, 000 cells per mouse) improved cardiac function following myocardial infarction, inducing endogenous cardiac regeneration in the infarcted myocardium. The de novo regenerated myocardium was thought to be derived from epicardial cells, which were positive for Wilms' tumor protein 1 expression. These findings were attributed to the sustained, local simvastatin release from the recruited SimNP‐loaded AdSCs in the infarcted myocardium rather than to the direct contribution of recruited AdSCs to tissue regeneration. SimNP‐loaded AdSCs may lead to a novel somatic stem cell therapy for IHDs. Stem Cells Translational Medicine 2019;8:1055–1067 Abstract : Simvastatin conjugated polymer nanoparticle‐loaded AdSCs induce cardiac regeneration.